1973
DOI: 10.1139/v73-479
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine N.M.R. Spectra of Sulfur, Phosphorus, and Silicon Fluorides: Hydrolysis and Intra- and Intermolecular Mechanisms of Fluorine Exchange

Abstract: The fluorine n.m.r. spectra of SF4, [(CH3)2CH]2NSF3, PF5:O(C2H5)2, SiF5−, SiF5:NH3−, and SiF5:HN(C2H5)2− have been recorded after treatment of glassware and reagents with [(CH3)3Si]2NH to remove H2O and HF impurities. A mechanism of intramolecular and intermolecular fluorine exchange, involving Lewis acid – Lewis base interaction and rapid equilibration of five and six coordinate geometries, is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…Although this study provides no direct evidence related to the mechanism of axial-equatorial exchange, the postulate that exchange occurs via intermediates 4 or 5 is consistent with our previous suggestion that the lowest energy pathway of axial-equatorial exchange in trigonal bipyramidal molecules involves Lewis acid-base interactions and rapid equilibration of five-and six-coordinate geometries (8). Since SiF,-samples do not exhibit For personal use only.…”
Section: Zntramolecular Axial-equatorial Exchangesupporting
confidence: 82%
See 1 more Smart Citation
“…Although this study provides no direct evidence related to the mechanism of axial-equatorial exchange, the postulate that exchange occurs via intermediates 4 or 5 is consistent with our previous suggestion that the lowest energy pathway of axial-equatorial exchange in trigonal bipyramidal molecules involves Lewis acid-base interactions and rapid equilibration of five-and six-coordinate geometries (8). Since SiF,-samples do not exhibit For personal use only.…”
Section: Zntramolecular Axial-equatorial Exchangesupporting
confidence: 82%
“…The relationship between coordination number and intern~olecular fluorine exchange may also be investigated by using a Lewis base, rather than a fluorine ligand, to vary the coordination number of silicon. In such an experiment it was found that addition of a large excess of NH, (10 M) to a sample containing Pr4N+SiF,-(0. inhibited fluorine exchange, presun~ably because SiF,-is converted to SiF,(NH,)- (7,8) and intern~olecular fluorine exchange between sixcoordinate SiF,(base)-and SF6'-is slow on the nmr time scale.…”
Section: Base and Intermolecular Fluorine Exchangementioning
confidence: 99%
“…In group 14, only a few monosubstituted products of [SiF 6 ] 2- like [SiF 5 (C 6 H 5 )] 2- , [SiF 5 (NH 3 )] - , [SiF 5 (NH(C 2 H 5 ) 2 )] - , cis -[SiF 4 (bipy)], cis -[SiF 4 (ox)] 2- , cis -[SiF 4 (mal)] 2- , and cis -[SiF 2 (ox) 2 ] 2- , , have been identified as octahedral species by 19 F NMR spectroscopy. For Ge only a few single fluoro complexes and the incomplete series, [GeF n X 6 - n ] 2- , n = 3−6, X = NCS - , and n =4−6, X = CN - , N 3 - , including the pairs of stereoisomers for n = 3 and 4, are known …”
Section: Main Group Elementsmentioning
confidence: 99%
“…Indeed, the low-temperature NMR of SF 4 shows two fluorine signals of equal area. Like other sulfuranes, SF 4 is a nonrigid molecule which undergoes rapid exchange of ligand positions as revealed by its dynamic NMR spectra at higher temperatures .…”
Section: Introductionmentioning
confidence: 99%